2011
DOI: 10.12968/ijtr.2011.18.11.631
|View full text |Cite
|
Sign up to set email alerts
|

Living with chronic obstructive pulmonary disease: experiences in northern regional Australia

Abstract: Objectives: This study aims to explore in depth the experience of living with chronic obstructive pulmonary disease (COPD) from the perspective of people with the condition in northern regional Australia. Methods: Qualitative research design was employed. Data was obtained from eight participants from a health service for chronic illness using semi-structured interviews to capture participants' diverse experiences. The interviews were audio-taped, transcribed and analyzed using a computer software programme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Similarly, while much of rural health discourse focuses on deficits in care and experience,46 and that respiratory care within the explored region is based on a rural generalist model, participants in this study did not speak of ‘missing out’ on services, information or access to specialists. Sossai et al described several negative factors influencing life with COPD (anxiety, depression, breathing and sleeping difficulties, reduction in daily/social activities and independence), but the impact of the rural context was generally limited to the associated climate 33. Goodridge’s commentary on this paper suggested that rural patients with COPD often experienced difficulty accessing self-management support and education 33.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Similarly, while much of rural health discourse focuses on deficits in care and experience,46 and that respiratory care within the explored region is based on a rural generalist model, participants in this study did not speak of ‘missing out’ on services, information or access to specialists. Sossai et al described several negative factors influencing life with COPD (anxiety, depression, breathing and sleeping difficulties, reduction in daily/social activities and independence), but the impact of the rural context was generally limited to the associated climate 33. Goodridge’s commentary on this paper suggested that rural patients with COPD often experienced difficulty accessing self-management support and education 33.…”
Section: Discussionmentioning
confidence: 88%
“…These influences are associated with reduced coping ability, decreased help seeking,40 the need to continually repeat medical history and are barriers to develop trusting relationships with health professionals 41. In comparison with other qualitative Australian studies into the patient’s experience of COPD, beneficial impacts were reported when patients felt supported by community members and health professionals,33 42 43 connected to people and nature,42 felt a strong sense of community43 and felt listened to by health professionals 44…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients further elaborated barriers such as fear of being too far away from home, worry about collapsing due to breathlessness, and anxiety related to unfamiliar places. 23 , 24 , 34 , 48 , 49 , 52 , 54 , 57 Physical activity revealed the illness in front of others, which further contributed to making physical activity a source of distress. 23 Fear of experiencing a panic attack was described as disabling, and patients were anxious of being too breathless, which ultimately limited their activities.…”
Section: Resultsmentioning
confidence: 99%